Pinnipeds and avian influenza: a global timeline and review of research on the impact of highly pathogenic avian influenza on pinniped populations with particular reference to the endangered Caspian seal (Pusa caspica) - Gadzhiev, Alimurad; Petherbridge, Guy; Sharshov, Kirill; Sobolev, Ivan; Alekseev, Alexander; Gulyaeva, Marina; Litvinov, Kirill; Boltunov, Ivan; Teymurov, Abdulgamid; Zhigalin, Alexander; Daudova, Madina; Shestopalov, Alexander (Frontiers in Cellular and Infection Microbiology, 2024)
This study reviews chronologically the international scientific and health management literature and resources relating to impacts of highly pathogenic avian influenza (HPAI) viruses on pinnipeds in order to reinforce strategies for the conservation of the endangered Caspian seal (Pusa caspica), currently under threat from the HPAI H5N1 subtype transmitted from infected avifauna which share its haul-out habitats. Many cases of mass pinniped deaths globally have occurred from HPAI spill-overs, and are attributed to infected sympatric aquatic avifauna. As the seasonal migrations of Caspian seals provide occasions for contact with viruses from infected migratory aquatic birds in many locations around the Caspian Sea, this poses a great challenge to seal conservation. These are thus critical locations for the surveillance of highly pathogenic influenza A viruses, whose future reassortments may present a pandemic threat to humans.